Award for Innovative Research Project "Moral distress and associations with health status and empathy in nursing personnel" - Karanikola, Maria (My University, 2026)
Award for Innovative Research Project, under the title "Moral distress and associations with health status and empathy in nursing personnel" Symposium of Nursing Research, Institution of Nursing Research and Health Politics Conference, Kalavrita, Greece.
Keywords: Sciences